Insights on mining the pangenome of Sphingobacterium thalpophilum NMS02 S296 from the resistant banana cultivar Pisang lilin confirms the antifungal action against Fusarium oxysporum f. sp. cubense - Ajesh, B. R.; Sariga, R.; Nakkeeran, S.; Renukadevi, P.; Saranya, N.; Alkahtani, Saad (Frontiers in Microbiology, 2024)
Introduction Fusarium wilt, caused by Fusarium oxysporum f. sp. cubense (Foc), poses a significant global threat to banana cultivation. Conventional methods of disease management are increasingly challenged, thus making it necessary to explore alternative strategies. Bacterial endophytes, particularly from resistant genotypes, are gaining attention as potential biocontrol agents. Sphingobacterium thalpophilum, isolated from the resistant banana cultivar Pisang lilin (JALHSB010000001-JALHSB010000029), presents an intriguing prospect for combating Fusarium wilt. However, its underlying biocontrol mechanisms remain poorly understood. This study aimed to elucidate the antifungal efficacy of S. thalpophilum NMS02 S296 against Foc and explore its biocontrol mechanisms at the genomic level. Methods Whole genome sequencing of S. thalpophilum NMS02 S296 was conducted using next-generation sequencing technologies and bioinformatics analyses were performed to identify genes associated with antifungal properties. In vitro assays were used to assess the inhibitory effects of the bacterial isolate on the mycelial growth of Foc. To explore the biomolecules responsible for the observed antagonistic activity, metabolites diffused into the agar at the zone of inhibition between Foc S16 and S. thalpophilum NMS02 S296 were extracted and identified. Results Whole genome sequencing revealed an array of genes encoding antifungal enzymes and secondary metabolites in S. thalpophilum NMS02 S296. In vitro experiments demonstrated significant inhibition of Foc mycelial growth by the bacterial endophyte. Comparative genomic analysis highlighted unique genomic features in S. thalpophilum linked to its biocontrol potential, setting it apart from other bacterial species. Discussion The study underscores the remarkable antifungal efficacy of S. thalpophilum NMS02 S296 against Fusarium wilt. The genetic basis for its biocontrol potential was elucidated through whole genome sequencing, shedding light on the mechanisms behind its antifungal activity. This study advanced our understanding of bacterial endophytes as biocontrol agents and offers a promising avenue for plant growth promotion towards sustainable strategies to mitigate Fusarium wilt in banana cultivation.